IN VITRO EVALUATION OF CHITOSAN AND ITS QUATERNIZED DERIVATIVE ON THE INHIBITION OF PENICILLIUM EXPANSUM GROWTH - Mendes, L. D.; Bresolin, J. D.; Assis, O. B. G.; de Britto, D. (Revista Brasileira de Engenharia de Biossistemas, 2016)
Chitosan of medium molar weight (400,000 gmol-1) from commercial origin and its quaternized water-soluble derivative N,N,N-trimethylchitosan were evaluated in laboratorial scale, in in vitro analyses, as inhibitors agents of Penicillium expansum growth. Formulations with polymer concentrations of 0.1; 1.0; 5.0 and 10.0 gL-1 were prepared and added to PDA solid and aqueous culture medium. The fungus strain was collected from decay fruits, harvested and inoculated in the medium with the polymers. Measurement of colony size growth (in solid medium) and germinated spore’s counting (in liquid medium using a Neubauer cell) indicated that both polymers act efficiently in reducing fungal infestation, nevertheless in distinct ways. The chitosan showed high efficiency in liquid medium while the derivative was more effective in solid medium, both at low concentrations (0.1 e 1.0 gL-1). The results were discussed based on chitosan accepted antimicrobial mechanisms, aiming potential topic applications on fruits in postharvest conditions.